Impact of green intellectual capital, green organizational culture, and frugal innovation on sustainable business model innovation: Dataset of manufacturing firms in Pakistan - Saad Mahmood Bhatti; Muhammad Zia ul Haq; Sara Kanwal; Zafir Khan Mohamed Makhbul (Data in Brief, 2024)
This dataset integrates and helps examine the impact of green intellectual capital (GIC) which comprises of green human capital (GHC), green structural capital (GSC), and green relational capital (GRC) on green organizational culture (GOC). Secondly, it enables the investigation of GOC as a mediation phenomenon between GIC and sustainable business model innovation (SBMI). Moreover, it highlights the moderation of frugal innovation (FGL) on GOC and SBMI relationship. An online survey was designed using Google forms to collect data from 345 middle/ senior management employees working in medium and large manufacturing firms in Pakistan. Unit of analysis is the organization; thus, each response represents one firm. SPSS and Smart PLS 4 were used for data analysis. Dataset demonstrates that GHC, GSC, and GRC positively impact GOC, which subsequently enhances SBMI. Moreover, effective implementation of FGL can bolster the effect of GOC on SBMI. The dataset is valuable as it can be reproduced and reanalyzed. It offers insights for professionals to revolutionize their innovation for environmental initiatives particularly in the manufacturing sector and train their staff to use modern eco-friendly ingenuities leading to enhanced business performance as well as sustainable development goals. Furthermore, the dataset holds significance for policymakers involved in implementing green economic revitalization programs, enabling them to offer incentives or penalties to encourage compliance.